PENGARUH MODEL PEMBELAJARAN TWO STAY TWO STRAY TERHADAP HASIL BELAJAR SISWA PADA MATERI REAKSI OKSIDASI DAN REDUKSI DI SMA BINA BANGSA ACEH BESAR - Teuku Badlisyah (UIN AR-RANIRY, 2018)
In the learning process, most students have difficulties to understand the chemistry subject that delivered by the teacher. One thing that caused the difficulties of student learning was the minimum used of an appropriate learning model by the the teacher. This study was conducted to know the influence of Two Stay Two Stray learning model towards the improving of student learning result of Oxidation and Reduction Reaction Material, the student activity, and student response towards the study model of Two Stay Two Stray in SMA Bina Bangsa. The sample in this research was the students in class X of SMA Bina Bangsa. This research used the quantitative approach with a design research of Pre-Eksperimen. Data collection was done by multiple choice test, observation and student response questionnaire. The result showed that there was an increasing in student learning that taught by using learning model of Two Stay Two Stray at the test of normality with a significant level X2 count < X2 table or 1.467 < 11,1 states that the test has a normal distribution, whereas the t test with significance level of Tcount > Ttable or 8.251 > 2.13 that states there was an influence towards the students study research by using the Two Stay Two Stray model, while by n-Gain test the average students reaches the high criteria. The observation result of student activity has increased from 79.14% at the 1st meeting to become 88.33% at the 2nd meeting, the students also have a positive response towards the application of Two Stay Two Stray model study on Oxidation and Reduction Reaction material, with the student response percentage of â€œYesâ€ was 84% which means the students were interested with the Two Stay Two Stray model study.